2022
DOI: 10.1108/tqm-07-2022-0236
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of organizational variables of quality 4.0 in digital transformation: the study of an Indian manufacturing company

Abstract: PurposeThe study aims to identify organizational variables of quality 4.0 for an Indian manufacturing company in the case of digital transformation. Furthermore, the organization enhances its quality 4.0 performances to its success based on the degree of relevance of these variables, insight into these variables and sub-factors to prioritize them.Design/methodology/approachInitially, two rounds of the survey were conducted with 11 decision-makers from the company made to receive organizational variables scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 89 publications
0
0
0
Order By: Relevance
“…Mittal et al . (2022) provided a comprehensive overview of Quality 4.0, including its background, OVs, key concepts and application areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Mittal et al . (2022) provided a comprehensive overview of Quality 4.0, including its background, OVs, key concepts and application areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have been conducted on Quality 4.0, focusing on its potential benefits and challenges. A literature review by Mittal et al . (2022) found that Quality 4.0 can enhance quality control, increase productivity and reduce costs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations